2015
DOI: 10.1007/s00520-015-2960-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress trajectories 1 year after a breast cancer diagnosis

Abstract: This study demonstrates that the majority of breast cancer patients in our study were resilient, with only a small percentage showing chronic acute stress. Because coping strategies, specifically anxious preoccupation, and not more stable variables played a main role in the prediction of acute stress trajectories, future preventive interventions should center in promoting more adaptive coping strategies in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The result that most older breast cancer survivors maintain good emotional and cognitive function over time is similar to observations in previous studies modelling trajectories with younger survivors . The fact that one‐third of older survivors had accelerated physical decline is in contrast to results in younger samples and is likely to represent normal aging processes, increased incidence of noncancer chronic illness with advancing age, and possible interactions between chronic illness and cancer and its therapies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The result that most older breast cancer survivors maintain good emotional and cognitive function over time is similar to observations in previous studies modelling trajectories with younger survivors . The fact that one‐third of older survivors had accelerated physical decline is in contrast to results in younger samples and is likely to represent normal aging processes, increased incidence of noncancer chronic illness with advancing age, and possible interactions between chronic illness and cancer and its therapies.…”
Section: Discussionsupporting
confidence: 80%
“…However, most longitudinal studies have studied change at the group level and were not able to identify underlying trajectories in QOL or predictors of subgroups at risk for poor QOL. Further, the few studies examining trajectories have generally only assessed a single aspect of QOL, mostly emotional distress or acute stress symptomatology, and shown distinct trajectories of distress following a breast cancer diagnosis that are consistent with patterns of adjustment to traumatic life events suggested by Bonanno . Some of these studies have also examined the psychological predictors of membership in a trajectory group, concluding that personal and social resources distinguish the different trajectories of the distress of breast cancer patients over time: Women with less self‐esteem and less personal control, lower sense of mastery, less optimism, higher trait and state anxiety or neuroticism, higher focus on symptoms and use of anxious preoccupation and cognitive avoidance as coping strategy, and less social support were more likely to be classified in the higher distress groups.…”
Section: Introductionmentioning
confidence: 98%
“…“Type C” personality was assessed in one paper that explored predictors of 4 different trauma symptom trajectories in the first year after diagnosis of breast (see explanation above). It predicted a “mild” trajectory.…”
Section: Resultsmentioning
confidence: 99%
“…31 One study reported that specific coping styles predicted cancer patients' trauma symptom trajectories in the first year after diagnosis. 53 This study identified 4 different trajectories of trauma symptoms on the basis of latent growth mixture modelling: resilient (low levels of symptoms at each measurement), delayed-recovered (initial low levels of symptoms that increased and then decreased), mild (initial moderate symptoms slowly decreasing over time), and chronic (persistent high levels of trauma symptoms). Coping by "anxious preoccupation" predicted "mild," "chronic," and "delayed-recovered" symptom trajectories.…”
Section: Self-esteemmentioning
confidence: 99%
“…Clinicians and researchers agree about the potentially traumatic impact of the illness, and many studies have shown high levels of cancerrelated psychologically based suffering in a substantial proportion of patients, even though only a minority develops a clinical or subclinical form of posttraumatic stress disorders (PTSDs) as defined by Diagnostic and Statistical Manual of Mental Disorders (5th ed. ;DSM-5;American Psychiatric Association [APA], 2013;Mehnert & Koch, 2008;Mitchell et al, 2011;Pérez et al, 2016). From this point of view, the study and implementation of research and intervention aimed at taking care of psychopathology reported by patients with cancer has become an area of fundamental et al, 2012).…”
mentioning
confidence: 99%